Evaluation of Mucous Retention Cyst Prevalence on Digital Panoramic Radiographs in the Local Population of Iran - Homa Rastegar; Fereshteh Osmani (Radiology Research and Practice)
Introduction. Inflammatory diseases and cysts such as mucous retention cysts (MRCs) and benign tumors include a large proportion of lesions of the mouth, teeth, and jaw. The most common complication of this lesion is sinusitis. Due to the high frequency of these cysts in panoramic radiography of patients referred to dentistry, this study aimed to evaluate the frequency of mucous retention cysts in the maxillary sinus on panoramic images of the local population in Birjand in the year 2020. Methods. In this descriptive research design study, 1624 digital panoramic radiographs of patients referred to the oral and maxillofacial radiology department of Birjand Dental School were selected randomly. Cases were evaluated in terms of MRC appearance by two oral and maxillofacial radiology specialists. Then, based on sex, location, and size of the cysts, the images were assessed. In the predesigned checklists, data were recorded. The MRC diagnosis was confirmed by observation of a dome-shaped radiopaque view on the floor or sinus walls with a smooth surface with no cortical margin. MRCs were categorized into one of three groups by size: 1- less than 10 mm, 2- between 10 and 20 mm, and 3- more than 20 mm. Bilateral or unilateral involvement of lesions was noted. Seasons of the year (P<0.05). There was no significant relationship between the month of the year and the prevalence of cysts (P>0.05). Results. MRCs were detected in 80 panoramic images of 1624 (9/4), of which 54 patients (67.5%) were male and 26 patients (32.5%) were female. Of those 34 (42.5%), the total cases were between 30 and 40 years old. Most cysts (58.8%) were in the right sinus, and their size was 10–20 mm mainly (43.4%). Based on the results, there was a significant relationship between the prevalence of MRCs with age and sex. Conclusions. Panoramic images are so helpful in MRC detection. In this study, the frequency of MRCs is the highest in males between 30 and 40 years old. These lesions are reported mainly as unilateral and solitary in spring.